2020
DOI: 10.15741/revbio.07.e968
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de dietas con harina de aguacate sobre lípidos en músculo, antioxidantes y expresión de genes en cerdos finalizados

Abstract: El objetivo de esta investigación fue valorar el nivel de inclusión de harina de aguacate (HA) 0, 5 y 10% en la alimentación de cerdos por 56 días antes del sacrificio a 109±4 kg, sobre efectos en la modulación de los lípidos, presencia de antioxidantes en el Longissimus dorsi y expresión de genes en los tejidos Longissimus dorsi e hígado. Se emplearon en cada dieta ocho cerdos machos de 55±3 kg de peso inicial, para compararlas bajo un diseño completamente al azar, con análisis de varianza y prueba de Tukey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…In this context, the Landrace and Yorkshire breeds are more efficient than the Duroc breeds in terms of ADG and FC during the finishing stage. Furthermore, this breed tends to deposit more fat than protein in the finishing stage [51]. This could explain the results reported in our study and other works [48], in which crosses with Duroc were used and no effect of FA.…”
Section: Productive Performance and Carcass Traitssupporting
confidence: 79%
See 1 more Smart Citation
“…In this context, the Landrace and Yorkshire breeds are more efficient than the Duroc breeds in terms of ADG and FC during the finishing stage. Furthermore, this breed tends to deposit more fat than protein in the finishing stage [51]. This could explain the results reported in our study and other works [48], in which crosses with Duroc were used and no effect of FA.…”
Section: Productive Performance and Carcass Traitssupporting
confidence: 79%
“…Likewise, multiple factors, such as purity, the vegetable origin of the FA evaluated [6,49] as well as the experimental conditions (ambient temperature and relative humidity) joined to the evaluation period, which determines nutrient utilization in pigs and may partially explain the differences between our results with Valenzuela-Grijalva study [6]. Even previous studies [48][49][50][51] have shown that breed and genetic line influence growth rate and productive performance parameters, such as feed conversion and feed intake. In this context, the Landrace and Yorkshire breeds are more efficient than the Duroc breeds in terms of ADG and FC during the finishing stage.…”
Section: Productive Performance and Carcass Traitsmentioning
confidence: 64%
“…This effect has been associated with a decrease in LDH (lactate dehydrogenase) activity and glycolytic fast fibers while increase gene expression of oxidative slow fibers and SDH (succinate dehydrogenase) activity [7,44,45] Respect to dietary inclusion of GPM, a reduction in marbling degree and a trend to increase loin area was observed. The reduction in intramuscular fat was also observed with other agro-industrial by-products (tomato, avocado meal, and citrus residues) which has been associated to its proximal composition that generate a nutrient contribution to the diet [37,46]. This results, can be related to some PCs (chlorogenic acid, caffeic acid, catechin, epicatechin, resveratrol) previously identified in GPM (Supplementary Figure S1) and in other research [44,47].…”
Section: Productive Performance and Carcass Traitssupporting
confidence: 70%
“…SO was compared only in the expression of the PPARG gene, the AM treatment had higher expression in five genes (ACACA, FASN, SCD, FASBP3 and SREBF1). Feeding the sheep with AM presented higher gene expression compared to CO and SO, which indicates physiological effects on lipid modulation in L. thoracis, in this sense Lemus-Avalos et al (2020), mention that gene expression associated with lipid metabolism is different in each animal species and according to each tissue. The increase in the PUFA ratio in L. thoracis muscle reduced the expression of FASN, SCD and SREBP1 genes when sunflower oil was used, similar to that reported by Mohan et al (2012), considering that the diet with GA tended to present a higher amount of PUFA than the diet with AM, the effect was similar when decreasing the expression of these genes in GA and comparing them with AM, a similar situation occurred in an evaluation in lambs where soybean, cotton and rapeseed meals were added to the diet with a decrease in PUFA in thoracic muscle and an increase in the expression of lipogenic genes (Wang et al, 2019).…”
Section: Resultsmentioning
confidence: 79%
“…Other alternatives in supplementation for domestic animals are oilseed oils, which are used in ruminant feed (Mapiye et al, 2013;Zsédely et al, 2012). Several studies indicate that sunflower oil (SO) in ruminants and avocado meal (AM) in pigs are modulators of intramuscular fat and blood metabolites, so they can be used as viable alternatives in animal feed (González-Jiménez et al, 2021;Lemus-Avalos et al, 2020;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%